La proporcionalidad de las penas en los delitos relacionados al tráfico de sustancias sujetas a fiscalización, ¿política criminal o populismo punitivo?. - Manobanda Miranda Nataly Lizeth (2024)
The purpose of this research is to study the most relevant dogmatic approaches of today in relation to "atypicality" as a negative element of the theory of crime, a theory that has been collected within the Comprehensive Criminal Organic Code in force since the year 2014, where it has been typified in art. 18 as a criminal offence, to typical, unlawful and guilty conduct to have a legal consequence in the form of a penalty. This research is based on the need for doctrinal scientific analysis of criminal sciences and criminal policy related to the proportionality of penalties related to crimes of trafficking in substances classified as subject to control since proportionality as part of the guarantees of due criminal process, constitutionally enshrined in the Montecristi constitution of 2008 in its article 76.6; In this sense, the objective of this investigation is to establish an appropriate legal study between the principle of proportionality and its application in substance trafficking crimes. The current criminal policy that has been established within the Ecuadorian state is a clear reflection of populist management, that is, a management of criminal sanctions under an approach of sympathy of the citizens and not under specific guidelines of an adequate criminal policy, which It has resulted in a collapse in the social rehabilitation system given that one factor has been that the penalties for drug trafficking crimes have been increased, with this type of crime currently affecting 28.19% of the prison population. Drug-related crimes are the one with the highest crime rate in the country, so the state's response has been manifested only in the increase of penalties, which is why when the Comprehensive Organic Penal Code was in effect in 2014, it established a penalty for This type of crimes on a minimum scale of two to six months, on a medium scale of one to three years, these have been modified in the 2019 reforms, establishing a sentence of 5 one to three years for minimum scale; and, for medium scale, a sentence of three to five years, based on the above, this research starts by studying whether the state's response in increasing the penalties for this type of crimes has been the correct option or, in turn, I had a populist court that has only led to the collapse of the social rehabilitation system. In Ecuador, by constitutional mandate, it is established that the consumer should not be penalized, given that it is considered a public health problem, so it is also necessary for this work to analyze the criminalization of by the state and its criminal policy. in the fight against organized crime and its link with drug trafficking; to demonstrate the criminal policy that has been based on crime control based on prison and the harshening of penalties to satisfy a certain sector of the electorate without responding to technical questions of an adequate criminal policy, which is why it has had effects in the current failed Ecuadorian prison system that has generated a lack of control for state authorities. For the development of this research, a qualitative method has been chosen, since it will be based on necessary data as it is a pure or basic research typical of legal sciences, which will help to complement qualitative techniques such as observation and interviews. to understand from a better perspective the problem posed for study. Key words: Proportionality, Drug Crimes, Criminal Populism, Criminology.